Маркетингові стратегії розвитку українського ринку освітніх послуг - Ткачова, Надія Петрівна; Клімов, Максим Володимирович (Національний університет "Одеська політехніка", 2025)
У статті досліджено сучасний стан та перспективи розвитку ринку освітніх послуг в Україні. Проаналізовано вплив цифрових інновацій, зокрема впровадження дистанційного та змішаного навчання, на трансформацію освітнього середовища. Проаналізовано сучасний стан ринку освітніх послуг в Україні, визначено основні тенденції його розвитку в умовах євроінтеграції, цифровізації та глобалізації. Особлива увага приділена змінам в структурі попиту та пропозиції освітніх послуг, адаптації закладів освіти до нових викликів, а також впливу демографічних, економічних та соціальних чинників на динаміку ринку. Визначено ключові проблеми, зокрема фінансування освіти, нерівний доступ до якісної освіти, міграція студентів і викладачів. Розглянуто роль дуальної освіти у підвищенні конкурентоспроможності випускників та адаптації освітніх програм до потреб ринку праці. Акцентовано увагу на необхідності гармонізації взаємодії між ринком освітніх послуг та ринком праці для подолання дисбалансів у підготовці фахівців. Окреслено основні виклики, зокрема демографічні зміни, міграційні процеси та вплив воєнного стану, що впливають на функціонування освітнього сектору. Запропоновано стратегічні напрями розвитку, включаючи модернізацію управлінських технологій, інтеграцію з міжнародними освітніми системами та підвищення якості освітніх послуг. Запропоновано напрями удосконалення національної політики в галузі освіти, з урахуванням досвіду країн ЄС та перспективи інтеграції України у європейський освітній простір. Автори підкреслюють необхідність інноваційних підходів до управління освітніми установами, розвитку дистанційних технологій та зміцнення партнерства між державою, бізнесом і освітніми структурами.

The article is aimed at a systematic analysis of the current state of the Ukrainian market of educational services, identifying its main challenges and opportunities for development in the conditions of war and global transformations, as well as formulating promising directions for the modernization of this area, taking into account national and international experience. Analysis results. The article analyzes the current state of the market of educational services in Ukraine, identifies the main trends in its development in the context of European integration, digitalization and globalization. Particular attention is paid to changes in the structure of supply and demand for educational services, adaptation of educational institutions to new challenges, as well as the impact of demographic, economic and social factors on market dynamics. migration of students and teachers. The main challenges are outlined, in particular demographic changes, migration processes and the impact of martial law, which affect the functioning of the educational sector. Strategic directions of development are proposed, including modernization of management technologies, integration with international educational systems and improvement of the quality of educational services. Directions for improving the national policy in the field of education are proposed, taking into account the experience of the EU countries and the prospects for Ukraine's integration into the European educational space. The authors emphasize the need for innovative approaches to the management of educational institutions, the development of distance technologies and the strengthening of partnerships between the state, business and educational structures. The results of the research are directly applicable in the practical activities of higher education institutions to increase competitiveness: the implementation of competitive strategies provides a stable advantage over other institutions and solves current strategic problems; in the field of adaptation to market changes: the introduction of hybrid forms of education and new technologies allows educational institutions to effectively respond to challenges related to the war with russia and other factors; for the development of strategic Management: the formation of strategic management models based on competitive advantages contributes to the sustainable development of educational institutions.
Marketing strategies for the development of the Ukrainian market of educational services
Keywords: трансформація освіти; освітні послуги; цифровізація освіти; інноваційні технології; вища освіта; освітні послуги; інноваційні технології; Україна; дистанційне навчання; ринок; market; educational services; digitalization of education; innovative technologies; higher education in Ukraine; transformation of education; distance learning